SCHOLARLY TEXT WRITING WORKSHOP: UNLOCKING WEAKNESSES IN ARTICLE WRITING - Dina Ramadhanti; Diyan Permata Yanda; Muhsyanur Muhsyanur (STKIP PGRI Sumatera Barat, 2021)
This activity is carried out to provide training in writing scientific articles worthy of publication in scientific journals. The method used is the lecture and question and answer method. From these activities, it was found that there were three weaknesses in writing scientific articles, namely: weaknesses in presenting research results in the form of scientific articles, grammatical problems, and not understanding paraphrasing techniques in writing. These three things can be overcome by frequent writing practices because writing requires practice not theory, increasing interest in reading scientific articles to be familiar with article models worthy of publication, and by itself will be accustomed to criticizing previous research findings.